(untitled) (Journal of the Bangladesh Agricultural University, 2014)
This study examined the profitability of beef cattle fattening in the northern char area of Bangladesh. A total of 150 cattle fatteners were randomly selected from two districts representing the highest concentration of fatteners in the char area. Socioeconomic data as well as data on beef fattening were collected from the people selected at Pabna and Sirajgonj district. Descriptive statistics was used to analysis the socioeconomics characteristics of beef producers, the profit function was used to determine the profitability of beef market and regression analysis was used to determine the factor affecting profitability of beef cattle. In spite of beef cattle production was profitable agribusiness most of the farmers adopt traditional beef fattening system for beef fattening target the cattle marketing during the Muslim festival Eid-ul-Azha. Profitability margin equals BDT 13,350.84 per cattle. The benefit cost ratio of the entire enterprise was 0.52 that means cattle fattening enterprise is profitable and feasible business enterprise. The major problems facing the farmers include high cost of feeds, inadequate credit facilities, disease attack, illegal use of human drugs for cattle fattening, price fluctuation and inadequate extension services. A policy and research emphasis should be geared toward feeds production at affordable price to the fatteners and fatteners should be educated on how to formulate local feeds to reduce cost and access to feeds for better efficiency and discourage to use human drugs, tablets and injection for cattle fattening. These findings can be used by the Ministry of Livestock and Fisheries Development extension agents to promote beef cattle fattening in areas where beef cattle fattening is not practiced in the country. DOI: http://dx.doi.org/10.3329/jbau.v12i1.21402 J. Bangladesh Agril. Univ. 12(1): 127-126, June 2014